Direct cloning approach for expression of an anti-cucumber mosaic virus single-chain variable fragment in plant - Chua, K.H.; Khalid, N.; Harikrishna, J.A.; Othman, R.Y. (2005)
An anti Cucumber Mosaic Virus (anti-CMV) single chain variable fragment (scFv) was constructed into a plant expression vector using self-designed primers. Initially, sequence information of the scFv was obtained through automated sequencing. Based on the sequence information, two primers with appropriate restriction endonuclease sites were designed to facilitate the clone construction. This technique allows insertion of the desired gene to replace the GUS second exon in pCAMBIA 1301, without the need to form a complete cassette including promoter and termination signal prior to cloning into the vector. After insertion of the construct into the plant system through Agroinfection, the foreign protein, anti-CMV scFv antibody was expressed in tobacco plants.